Cartografie implicite e mappe di comunità: per una diversa classificazione dei Beni culturali - Vincenzo Esposito (EtnoAntropologia)
This article is about: Cultural anthropology, issues of power and definition of Cultural Heritage; religious rituals as spontaneous maps, implicit to local cultural contexts; «Parish maps» as local tool to survey and describe the cultural heritage of the area; role of the anthropologist and work with informants.